PERAN KOMITE SEKOLAH DALAM MANAJEMEN BERBASIS SEKOLAH DI SD ISLAM TERPADU BUAH HATI KABUPATEN PEMALANG - Amarin Amarin; Sunandar Sunandar; Noor Miyono (Jurnal Manajemen Pendidikan (JMP), 2016)
The purpose of this research is to gain an overview of the role of the school committee in the implementation of School Based Management in Elementary School Buah Hati District of Pemalang. The focus of research is the role of the school committee in the implementation of School Based Management with sub focus the role of the school committee as a conduit of consideration, the school committee as a support, the school committee as a controller, the school committee as a mediator in Elementary School Buah Hati District of Pemalang.Results showed the role of communities in School Based Management has a strategic role means that the school committee acts as a conduit of consideration in the form of ideas, input, aspirations, involvement in school programs, serve as a support in terms of funding, supporting school activities, imaging either to the surrounding community, the role of controlling which act as watchdogs of the budget in the form of reports, supervisory activities, acting as a liaison between multiple mediators that school with parents, education authorities and the public. Elementary School Buah Hati has a principle of independence, accountability, transparency, and strong partnerships that school that provides easy access to information to the school community and the public on what is being done with school by utilizing various communication channels. Constraint of the school committee in the implementation of school-based management is the lack of communication between the school and the school committee because of lack of time owned by the school committee.